2009
DOI: 10.1016/j.cyto.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating IL-8 is associated with reduced IGF-1 and related to poor metabolic control in adolescents with type 1 diabetes mellitus

Abstract: Background-A dysregulated growth hormone (GH)/insulin-like growth factor 1 (IGF-1) axis is well-recognized in children and adolescents with type 1 diabetes mellitus (T1DM). Decreased IGF-1 levels can also be found in chronic inflammatory diseases, while hyperglycemia promotes inflammatory cytokine production. Therefore, inflammatory cytokines may link poor metabolic control with GH/IGF-1 axis changes. This study examined the relationship between serum inflammatory cytokines and IGF-1 in adolescents (age 13-18)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 45 publications
3
30
0
1
Order By: Relevance
“…Previous studies reported lower serum IGF-1 along with higher inflammatory cytokines and lower bone mineral density in T1DM patients with poor glycemic control than those with good glycemic control [2931]. We first confirmed that the proliferation and osteogenesis of these diabetic BMSCs and PDCs were differentially impaired and these impairments were exacerbated in high glucose cultures.…”
Section: Introductionsupporting
confidence: 76%
“…Previous studies reported lower serum IGF-1 along with higher inflammatory cytokines and lower bone mineral density in T1DM patients with poor glycemic control than those with good glycemic control [2931]. We first confirmed that the proliferation and osteogenesis of these diabetic BMSCs and PDCs were differentially impaired and these impairments were exacerbated in high glucose cultures.…”
Section: Introductionsupporting
confidence: 76%
“…Human pancreatic islets produce and secrete the proinflammatory CXCL8 and CXCL1 ligands (12,15,17,22,23), whereas lipopolysaccharide-induced production of CXCL8 by neutrophils is increased in prediabetic and T1D patients. In parallel, circulating concentrations of CXCL8 are elevated in children with T1D compared with nondiabetic controls (24)(25)(26). Specifically, concentrations of CXCL8 correlate with glycemic control; higher concentrations are associated with poor or inadequate glucose control.…”
Section: Diabetesdiabetesjournalsorgmentioning
confidence: 83%
“…In fact, pancreatic islets produce and secrete the CXCR1/2 chemokine ligands (named CXCL8, CXCL1, and CXCL2) in response to proinflammatory cytokines (12,15,17,22,23). Furthermore, the concentration of CXCR1/2 ligands is elevated in the blood of both rodents and humans with autoimmune diabetes (24)(25)(26); most important, recent reports support the notion that neutrophils (the major target of CXCR1/2 inhibitors) play a key role in the etiopathogenesis of T1D (27)(28)(29). We therefore extensively characterized the consequences of CXCR1/2 inhibition on inflammation-and autoimmunity-mediated diabetes in preclinical models.…”
mentioning
confidence: 99%
“…Moreover, the low levels of insulin-like growth factor-1 (IGF-1) [19,20,[28][29][30][31] and vitamin D [32], which also usually accompany diabetes, may be additional factors responsible for poor bone health (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%